Implications of diverging social and private discount rates for investments in the German power industry: a new case for nuclear energy? - Christoph Heinzel (Technische Universität Dresden, Fakultät Wirtschaftswissenschaften, 2008)
For power-plant investments, utilities rely after liberalisation on private financial markets, which are in general distorted. The (related) split of social and private time-preference rates provides a new reason for a welfare-enhancing policy intervention, complementary to environmental policy (Heinzel and Winkler 2007). This paper quantifies it and studies its relevance for the German power industry around 2015. The distortions remain moderate as compared to other investment subsidies. However, in contrast to environmental policy alone, its additional implementation makes nuclear power the first option even in the nuclear high-cost scenario. Both policies enhance ecological structural change, which end-of-pipe abatement delays.
Keywords: Q48; D92; H23; H43; 330; distorted time preferences; environmental and technology policy; conventional energy technologies; Investitionsrisiko; Kernkraftwerk; Kernenergiepolitik; Forschungs- und Technologiepolitik; Return on Investment; Zeitpräferenz; Industrieller Strukturwandel